Pemanfaatan Kecerdasan Buatan sebagai Upaya Pengembangan Media Pembelajaran Berbasis Multimedia - Dadang Sudrajat; Ririt Dwiputri Permatasari; I Made Sondra Wijaya; Antonius Edy Setyawan; Novi Rahayu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The use of artificial intelligence as a form of innovation carried out by an educator during the learning process by following technological developments in the era of society 5.0. Multimedia-based learning media makes it easy for educators and students. This research uses a qualitative descriptive research method using primary data and secondary data for later analysis. Primary data was obtained from observations several educators, while secondary data was obtained from literature study in the form of references to scientific literature. The research results show that in the era of society 5.0, many educators are utilizing artificial intelligence applications to make their work easier during the learning process. One form of artificial intelligence used in developing learning media is GPT chat (Generative Pre-Training Transformer). The GPT chat application is widely used by educators because of its nature of providing structured answers in a short period of time. GPT chat can help educators determine learning media content according to the theme determined by the educator, so educators only need to create presentation slides based on content created from GPT chat. Educators need to understand the prompts so that the results of the learning media content provided by GPT chat can be effective. This research aims to determine the use of artificial intelligence to develop multimedia-based learning media among educators. Therefore, educators need to integrate learning with technology so that the credibility of educators' competence increases. Keywords: chat GPT, content, learning process